SPE Annual Technical Conference and Exhibition 2013
DOI: 10.2118/166325-ms
|View full text |Cite
|
Sign up to set email alerts
|

Full-Scale Laboratory Study of the Impact of Drilling Fluid Composition and Properties on Penetration Rates in Brazilian Pre-Salt Carbonates

Abstract: Full-scale laboratory drilling tests investigated the drilling performance potential of a number of different drilling fluids in three analogue rocks for the pre-salt formations offshore Brazil: Bonne Terre dolomite, Carthage limestone, and Navajo Gold travertine. High-pressure drilling tests were performed in each of these rocks using a total of nine different drilling fluids, including a synthetic-based fluid used as reference for performance comparison. There was a consistent ranking of drill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, it can be inferred from comparison of the visual single point cutter and full scale drilling test results that the fluid properties may well influence the drilling process in salt. There is much debate about the extent to which solids may or may not influence the drilling process, as summarized by Curry et al (2013). Their study indicated that solids content per se did not directly influence penetration rates in the hard carbonates tested.…”
Section: Discussionmentioning
confidence: 99%
“…However, it can be inferred from comparison of the visual single point cutter and full scale drilling test results that the fluid properties may well influence the drilling process in salt. There is much debate about the extent to which solids may or may not influence the drilling process, as summarized by Curry et al (2013). Their study indicated that solids content per se did not directly influence penetration rates in the hard carbonates tested.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the combined problems of compaction disequilibrium and salt tectonics. complex stress patterns were created in the formations surrounding the salt structures which led to rubble zones and recumbent beds [10,11,12]. Therefore.…”
mentioning
confidence: 99%